Pengaruh Kualitas Jasa Dengan Kepuasan Pelanggan Di RS Husada Jakarta - Andyan Pradipta Utama (Jurnal Ekonomi, 2016)
The purpose of this study was to determine the relationship of service quality with patient satisfaction in Husada hospital Jakarta in order to provide a draft proposal regarding the quality of service in an effort to improve customer satisfaction. The variables of this study are the quality of service (independent variable) and customer satisfaction (dependent variable). Subjects were patients at the Husada hospital Jakarta totalling 100 patients who were assigned to the non-probability sampling method accidental sampling. Measurements were made using a scale of Quality of Service which consists of 20 items, and the Patient Satisfaction scale consisted of 12 items that are already on the validity and reliability. By using the technique of linear regression through SPSS for Windows version 21.0 was obtained in the regression R = 0.78 and R square = 0.609, p = 0.000 (p <0.05) indicating that patient satisfaction positively and significantly related to the quality of service equal to 0.780 and the role of service quality variables are able to explain the variable of 60.9% patient satisfaction. The study hypothesis which states "quality of care can improve patient satisfaction in Husada hospital Jakarta ", is accepted. This means the better the quality of service will be followed by increased patient satisfaction in Husada hospital Jakarta.